Resistin secreted by porcine alveolar macrophages leads to endothelial cell dysfunction during Haemophilus parasuis infection - Kexin Hua; Tingting Li; Yanling He; Aohan Guan; Liying Chen; Yuan Gao; Qianshuan Xu; Haoyu Wang; Rui Luo; Ling Zhao; Hui Jin (Virulence)
Haemophilus parasuis (H. parasuis) causes exudative inflammation, implying endothelial dysfunction during pathogen infection. However, so far, the molecular mechanism of endothelial dysfunction caused by H. parasuis has not been clarified. By using the transwell-based cell co-culture system, we demonstrate that knocking out resistin in porcine alveolar macrophages (PAMs) dramatically attenuated endothelial monolayer damage caused by H. parasuis. The resistin secreted by PAMs inhibited the expression of the tight junction proteins claudin-5 and occludin rather than the adherens junction protein VE-cadherin in co-cultured porcine aortic endothelial cells (PAECs). Furthermore, we demonstrate that resistin regulated claudin-5 and occludin expression and monolayer PAEC permeability in an LKB1/AMPK/mTOR pathway-dependent manner. Additionally, we reveal that the outer membrane lipoprotein gene lppA in H. parasuis induced resistin expression in PAMs, as deleting lppA reduced resistin expression in H. parasuis-infected PAMs, causing a significant change in LKB1/AMPK/mTOR pathway activity in co-cultured PAECs, thereby restoring tight junction protein levels and endothelial monolayer permeability. Thus, we postulate that the H. parasuis lppA gene enhances resistin production in PAMs, disrupting tight junctions in PAECs and causing endothelial barrier dysfunction. These findings elucidate the pathogenic mechanism of exudative inflammation caused by H. parasuis for the first time and provide a more profound angle of acute exudative inflammation caused by bacteria.